Optimization of round shape floating LNG supply chain efficiency with simulation modeling [electronic resource] - Sanusi, 1984-; Eng, Jaswar Koto, supervisor; Azanizawati Ma'aram (2013)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Industri)) - Universiti Teknologi Malaysia, 2013